Social Media Marketing And Brand Equity Against Coffee Purchase Intentions - Yundi Permadi Hakim; Muh. Alvianto Putra Arizandi Sadarrudin; Burhanuddin Burhanuddin (International Journal of Economics and Management Research, 2023)
This study investigates the impact of Social Media Marketing and Brand Image on purchasing intentions for DELKOFF Brand coffee products. A survey research model is employed to collect data. The findings indicate that Social Media Marketing and Brand Equity have a significant influence on purchasing intentions. Moreover, it is found that social media-based marketing activities through online marketplaces are particularly effective during the pandemic. Both Social Media Marketing and Brand Equity contribute to increased sales. Management should emphasize marketing efforts via social media platforms to enhance product sales. This study solely examines two variables: Social Media Marketing and brand equity.